2019
DOI: 10.1111/jcmm.14170
|View full text |Cite
|
Sign up to set email alerts
|

Depression in sleep disturbance: A review on a bidirectional relationship, mechanisms and treatment

Abstract: Sleep disturbance is the most prominent symptom in depressive patients and was formerly regarded as a main secondary manifestation of depression. However, many longitudinal studies have identified insomnia as an independent risk factor for the development of emerging or recurrent depression among young, middle‐aged and older adults. This bidirectional association between sleep disturbance and depression has created a new perspective that sleep problems are no longer an epiphenomenon of depression but a predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
476
3
32

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 689 publications
(555 citation statements)
references
References 125 publications
44
476
3
32
Order By: Relevance
“…Our findings augment evidence of an inverse association between sleep and depressive symptoms (39,(41)(42)(43)45,52,53) and conflict with studies that found no prospective effect (54,77)or an effect in females only (46,47). Once considered a core symptom or comorbidity of depressive disorders, some now identify sleep problems as both a prodromal manifestation and an independent risk factor for subsequent episodes, predicting the occurrence and outcome of depressive disorders (78). In fact, given the inadequacy of treatments for youth depression (79), sleep therapy has been suggested as an intervention for adolescent MDD (79).…”
Section: Discussioncontrasting
confidence: 66%
“…Our findings augment evidence of an inverse association between sleep and depressive symptoms (39,(41)(42)(43)45,52,53) and conflict with studies that found no prospective effect (54,77)or an effect in females only (46,47). Once considered a core symptom or comorbidity of depressive disorders, some now identify sleep problems as both a prodromal manifestation and an independent risk factor for subsequent episodes, predicting the occurrence and outcome of depressive disorders (78). In fact, given the inadequacy of treatments for youth depression (79), sleep therapy has been suggested as an intervention for adolescent MDD (79).…”
Section: Discussioncontrasting
confidence: 66%
“…Our findings augment evidence of an inverse association between sleep and depressive symptoms (2,37,(39)(40)(41)43,50,51) and conflict with studies that found no prospective effect (52,73)or an effect in females only (44,45). Once considered a core symptom or comorbidity of depressive disorders, some now identify sleep problems as both a prodromal manifestation and an independent risk factor for subsequent episodes, predicting the occurrence and outcome of depressive disorders (74). In fact,…”
Section: Conditional Change Modelscontrasting
confidence: 66%
“…One possible explanation for the association between depression and changes of working schedules is that worsening of depressive symptoms in relation to night work may be more easily recognizable than other disorders, such as hormonal dysfunction. Furthermore, adequate sleep is one of the non-pharmacological therapies in the treatment of depression (48).…”
Section: Discussionmentioning
confidence: 99%